PEMIKIRAN AQIDAH AHLUSSUNNAH WAL JAMA’AH SYEKH MUHAMMAD AZHARI AL-FALIMBANI DALAM NASKAH PALEMBANG 1842 - Abdul Azim Amin (Fakultas Adab dan Humaniora UIN Raden Fatah, 2013)
Abstract: Palembang has been known as a center of maritime Malay - Javanese kingdom since the mid- 17th century AD which has the legislation